High perfomance audio power amplifiers for music performance and reproduction - Duncan, Ben A.M.I.O.A
Power amplifiers and their performance lie at the heart of audio engineering and provide some challenging problems for the engineer. Ben Duncan's experience, as an audio consultant, analog electronics designer and author, give him an unique insight into this difficult but rewarding field. Linking analog electronics, acoustics, heat and music technology; high-end hi-fi and professional PA and recording studio use; theory, modelling and real-world practice; design and repair; the old and the new, the mainstream and the specialised, this comprehensive guide to power amps is a core reference for a.